2019
DOI: 10.21240/mpaed/36/2019.11.11.x
|View full text |Cite
|
Sign up to set email alerts
|

The Fairy Tale of the Digital Natives

Abstract: Der Zielgruppe heutiger Hochschulbildung werden oft vorschnell weitreichende Kompetenzen im Umgang mit zunehmender Digitalisierung von Arbeitswelt und Alltag zugeschrieben. Das vorliegende Papier betrachtet dies kritisch und versucht sich der Frage zu widmen, wie Hochschulbildung den digitalen Wandel adressieren, begleiten und Studierende so zur beruflichen Kompetenz und aktiven gesellschaftlichen Teilhabe befähigen kann. Dies geschieht unter Einbezug des Curriculum 4.0-Projekts «Medizin im digitalen Zeitalter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…In addition, the developed content makes the learning success visible. Due to the different perspectives of the heterogeneous group of participants – students as well as teachers – diverse experiences and opinions become visible [ 7 ], [ 12 ]. The contributions will be inserted into an EDU version of the e-book after completion of the elective subject.…”
Section: Teaching Conceptmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the developed content makes the learning success visible. Due to the different perspectives of the heterogeneous group of participants – students as well as teachers – diverse experiences and opinions become visible [ 7 ], [ 12 ]. The contributions will be inserted into an EDU version of the e-book after completion of the elective subject.…”
Section: Teaching Conceptmentioning
confidence: 99%
“…This was also shown in a study conducted by the “Hochschulforum Digitalisierung” (University Forum for Digitisation), in which only 21% of the students were rated as “digital allrounders”. The majority of students gained experience primarily from a passive, consuming role and did not actively influence the digital environment [ 7 ], [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another study showed that although medical students had a positive view of digitization in the healthcare sector, they felt that they had little to no preparation for it during their studies [6]. These circumstances pose great challenges to existing structures such as teaching and learning methods [7]. While preparation for digital competencies is required [8], it is only partially addressed in the German National Competence-based Learning Objectives Catalog for Medicine (NKLM) 2.0 (https://nklm.de, accessed on 18 January 2023), which is not currently required to be implemented on a mandatory basis.…”
Section: Introductionmentioning
confidence: 99%